Development of sector-based ecological landscape guides within the framework of European landscape convention. The case of Sugla Lake in Turkey - Uzun, Osman; Cetinkaya Ciftcioglu, Gulay Cetinkaya; Nemutlu, Füsun Erduran; Ilke, E. Figen; Açıksöz, Sebahat; Açıksöz, Sebahat (Scibulcom Ltd. jbalkta@gmail.com 7 Nezabravka, PO Box 249 Sofia 1113, 2016)
According to the European Landscape Convention, each contracting country, ratified the ELC, is responsible for integrating its landscape protection, planning and management strategies into other sectoral plans such as urbanisation, agriculture and forestry. Purpose of this study is to develop sector-based (agriculture, forestry and urbanisation) ecological landscape guides by evaluating natural and cultural landscape components of the region of Sugla lake located in Turkey. Major objectives of the study include: determination of natural and cultural landscape characteristics and analysis of the functions (e.g. erosion process, infiltration, habitat and biodiversity). A range of dataset (e.g. geological and coordination of information on the environment land cover maps and questionnaire) was used to conduct the study. Method of the study consists of three stages: inventory, analysis and assessment. Major natural (e.g. flora and habitat distribution) and cultural (e.g. historical important areas and cultural heritage) landscape components of the region were identified and mapped in the first stage. Natural (erosion process, infiltration and biodiversity) and cultural (e.g. cultural heritage) landscape functions, which form the basis of the sector-based ecological landscape guides, were analysed and mapped by adapting a landscape ecology-based approach in the second stage. The ecological landscape guides for forest, agriculture and settlement sectors were determined by overlapping the delineated maps (e.g. erosion risk, infiltration and habitat) in the final section. We hope that the sector-based ecological landscape guides can be an effective tool particularly in the management of natural resources embedded in each sector by policy makers. © 2018 Elsevier B.V., All rights reserved.
Keywords: Ecological Landscape Guide; Landscape Planning; Sugla Lake; Turkey